Tomographic evaluation of prevalence, position, and diameter of the intraosseous branch of the posterior superior alveolar artery in fully edentulous individuals - De Oliveira, Guilherme José Pimentel Lopes; Abdala, Marciel Antônio; Nary-Filho, Hugo; Sakakura, Celso Eduardo; Garcia, Valdir Gouveia; Leite, Felipe Coletti (Wolters Kluwer, 2017)
The objective of this study was to evaluate the presence, position, and diameter of the intraosseous branch (IObr) of the posterior superior alveolar artery in fully edentulous patients. Two-hundred five computed tomography scans of fully edentulous patients were analyzed. The presence of the IObr was investigated in the coronal plane at the lateral wall of the maxillary sinus. In patients in whom the IObr was detected, the artery diameter was measured, and the distance from the artery to the bone crest of the alveolar ridge, the maxillary sinus floor, and the distance of the maxillary sinus floor to the bone crest of the alveolar ridge were measured as well. A descriptive statistical analysis of these parameters was conducted. The IObr was identified in the maxillary sinus in 105 tomography images (51.2%), and its diameter varied between 0.8 and 3.3mm (1.29±0.49 mm). The IObr presented with an artery diameter less than 1mm in 29% of the patients, between 1 and 2mm diameter in 61% of the patients and with a diameter larger than 2mm in 10% of patients. Regarding the IObr topography, the distance from the artery to the floor of the maxillary sinus was 9.62±4.59 mm, and the distance from the artery to the top of crestal bone was 15.15±4.47 mm. At least 10% of edentulous patients are at risk of bleeding complications during interventions in the maxillary sinus.
Keywords: Ct scan; Sinus lift augmentation; Surgical complications; Vascularization